DNA analysis of Ornithine Transcarbamylase (OTC) deficiency in South African patients - Swarts, Liezel Catharine (Division of Chemical Pathology, 2018)
Hyperammonaemia is not an infrequent presentation in the newborn or neonatal period. While the majority are transitory in nature and due to infective processes or liver pathology/immaturity, a significant number are due to defects in enzymes of the urea cycle. This cycle has evolved to cope with waste nitrogen disposal and the de novo synthesis of arginine. There are five distinct enzymatic steps in the urea cycle, and defects in each, result in a biochemically distinct disease. Four of these diseases, deficiencies of carbamyl phosphate synthetase (CPS), ornithine transcarbamylase (OTC), argininosuccmic acid synthetase (ASS), and argininosuccinate lyase (ASL) can present dramatically within the first 24 to 48 hrs of life with progressive lethargy, hypothermia and apnea, all related to very high plasma ammonia levels. These diseases may also present later in infancy, childhood and adulthood with hyperammonemia and episodic mental status changes. The fifth defect, arginase deficiency presents as progressive spastic quadriplegia and mental retardation but with milder elevation of blood ammonia levels. The molecular genetics of these disorders in South Africans has not been explored and there is thus very little information on phenotype/genotype relationships, specific for citizens of this country. This study aims to correct this imbalance and has concentrated initially on OTC deficiency, which is X-linked and therefore the most common defect encountered. Initial work on this project has concentrated on subjects with a classical X-linked OTC phenotype.